No Product is an Island: The Case of Incontinence Pads in a Nursing Home - Petersen, Morten Krogh; Ankerstjerne, Victoria; Bubinek, Ruby; Cimpan, Ciprian (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
This paper critically examines product durability through an ethnographic study of incontinence pad usage in a Danish municipal nursing home. By focusing on incontinence pads—which are referred to as “diapers” in this setting—we demonstrate that their durability cannot be understood in isolation from their surrounding environment. Instead, diapers attract auxiliary products, which, when integrated into the care practices of the nursing home, take part in enacting the diapers’ durability in distinct ways. We conceptualize these enactments as either supporting or challenging the durability of the diapers. Combining this ethnographic work with design theorist Arturo Escobar’s interweaving of ontological relationality and design theory, we argue that durability should not be viewed as an inherent property of an object or as determined solely by its human users. Instead, we propose understanding durability as a relational effect that emerges from situated sociomaterial practices. This analytical move challenges modernist assumptions that separate subjects from objects and offers a more nuanced framework for analyzing product durability. Future research on product durability would benefit from adopting this relational approach, as it opens—we hope to show—new ways of thinking and designing with sociomaterial practices and for product durability.